(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This work shares the experiences of a research teacher at Escola Municipal Tatiana Chagas Memória, located in Jardim Maravilha, Guaratiba/RJ. Taking place from June 19th to December 20th, 2023. The action research proposes an education based on the pillars of Human Rights, Natural Rights and Inclusion, defending a flexible approach that incorporates different languages ​​and tools. The methodology adopted had Art Based Research (ABR) as its central axis, which incorporates different approaches. This research was guided by the theory proposed by economist Alberto Acosta in his book “Bem Viver” (2016), “Carta da Terra” (1992), and by Edward Wilson’s concept of Biophilia (1984). To facilitate the investigation, tools such as Design Thinking and the Affective Tree were used. With the aim of meeting the Sustainable Development Goals (SDGs).